2017
DOI: 10.4081/jbr.2017.6279
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different circuit training protocols on body mass, fat mass and blood parameters in overweight adults

Abstract: Benefits of exercise are known for a long time, but mechanisms underlying the exercise mode recommendations for specific chronic cardiovascular diseases remain unclear. The aim of this study was to compare the effects of different circuit training protocols in order to determine which is the best for weight loss and for specific overweight-related disorders. Forty-five female sedentary overweight participants from 20 to 50 years (average 31.8±11.2) were enrolled and assigned to three different groups; each gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 7 publications
2
10
0
1
Order By: Relevance
“…However, no significant changes occurred in FBS, HDL, TC, and WHR (P > 0.05). These findings are consistent with that of Cardoso et al ( 8 ), Contro et al ( 21 ), Lee et al ( 22 ), Taghizadeh et al ( 23 ), and Martin et al ( 24 ), and inconsistent with Zhou et al ( 14 ) and Narayani et al ( 2 ).…”
Section: Discussionsupporting
confidence: 84%
“…However, no significant changes occurred in FBS, HDL, TC, and WHR (P > 0.05). These findings are consistent with that of Cardoso et al ( 8 ), Contro et al ( 21 ), Lee et al ( 22 ), Taghizadeh et al ( 23 ), and Martin et al ( 24 ), and inconsistent with Zhou et al ( 14 ) and Narayani et al ( 2 ).…”
Section: Discussionsupporting
confidence: 84%
“…However, these programs had no significant effects on low-density lipoprotein, total cholesterol, and triglyceride. These results are consistent with the findings of Freitas et al and Contrò et al [33,34]. However, it is inconsistent with the findings of Olson and associates [35].…”
Section: Discussionsupporting
confidence: 75%
“…They concluded that total cholesterol level and triglyceride level decreased significantly. Contrò et al reported that 12 weeks of circular aerobic exercises and trampoline exercises led to significant decrease in body weight, body fat percentage, and lowdensity lipoprotein in women aged 20 to 50 years [33].…”
Section: Discussionmentioning
confidence: 99%
“…It is notable that a large part of the gymnasts had the variant predisposing to greater accumulation of lipids, so it is important to emphasize that it is necessary to be mindful of eating habits and lifestyle in order to prevent the onset of overweight [20]. No statistically significant correlation between genotype and bMI was found.…”
Section: Discussionmentioning
confidence: 95%